Evaluation Of The Effect Of Compost, EDTA And Microorganisms On The Removal Of Heavy Metals And Arsenic From A Contaminated Soil - K. Vaxevanidou (Society for Mining, Metallurgy & Exploration, 2005)
A combined chemical and biological treatment for the removal of heavy metals and arsenic from a contaminated soil was studied as a potential method for soil remediation. Small scale and column tests were conducted in order to ex-amine the effect of plant-compost and Na2CaEDTA addition on a calcareous soil highly contaminated with heavy metals and arsenic. EDTA is known to be an efficient leaching agent of heavy metals from contaminated soils but has no effect on arsenic. Compost tea on the other hand contains humics that can leach several iron compounds including Fe(III)-oxides and thus can extract arsenic bound to these oxides. The action of Fe(III)-respiring bacteria D.palmitatis was also evaluated for the reduction of iron oxides and compared to simple chemical treatment in the presence of compost in small scale tests. Results indicated that the addition of compost and EDTA into soil pulp lead to the predominance of reductive conditions and the simultaneous dissolution of both heavy metals and arsenic at high percentages. The presence of D.palmitatis did not further enhance the reductive dissolution of Fe(III)-oxides by compost and EDTA as it was observed in the inoculated samples. Column tests using soil as received revealed that, although the extraction of metals seems to be a slow process, compost is an effective oxygen barrier that promotes the reductive dissolution of iron oxides and the subsequent arsenic release together with the dissolution of heavy metals by EDTA.